2021
DOI: 10.3892/ol.2021.12794
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‑2 expression is associated with chemoresistance through cancer stemness property in hypopharyngeal carcinoma

Abstract: Cyclooxygenase-2 (COX-2) is one of the two isoforms of COX, an enzyme that catalyzes the conversion of arachidonic acid to prostaglandins. COX-2 is associated with the progression in various types of cancer, and its expression has been associated with a poor prognosis in head and neck squamous cell carcinoma (HNSCC). Furthermore, COX-2 expression has been associated with resistance to anticancer drugs. However, the precise mechanism of COX-2 for chemoresistance in HNSCC has not been fully elucidated. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Many studies have confirmed single genetic markers associated with chemotherapy sensitivity in HPSCC. For instance, COX-2 expression has been found to be associated with chemoresistance through the cancer stemness property (Saito et al, 2021). The ctDNA might play a significant role in DDP resistance in HPSCC by amplifying related functional genes (Lin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed single genetic markers associated with chemotherapy sensitivity in HPSCC. For instance, COX-2 expression has been found to be associated with chemoresistance through the cancer stemness property (Saito et al, 2021). The ctDNA might play a significant role in DDP resistance in HPSCC by amplifying related functional genes (Lin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating the effects of COX-2 inhibition in hypopharyngeal cancer resulted in deceased expression of genes associated with CSCs and reduced sphere formation. Tumor viability was also decreased and these results were improved by the addition of docetaxel ( Saito et al, 2021 ). Dong et al demonstrated that inhibition of Bromo- and Extra-Terminal domain (BET) results in an unanticipated impairment of super enhancers and reduced stemness in HNC ( Dong et al, 2021 ).…”
Section: Targeting Cancer Stem Cellsmentioning
confidence: 99%
“…Proponents of the cancer stem cell model argue that because CSCs are thought to be relatively resistant to radiation and chemotherapy; they evade initial treatment modalities and subsequently are able to recreate the heterogeneous tumor. As such it is this small subset of cells that needs to be targeted in order to eradicate the tumor ( Bao et al, 2006 ; Dick 2008 ; Al-Assar et al, 2009 ; Mroz et al, 2013 ; Dionne et al, 2015 ; Subramanian et al, 2017 ; Zonga et al, 2018 ; Hu et al, 2019 ; Shibata and Hoque 2019 ; Keysar et al, 2020 ; Saito et al, 2021 ). More recently there has been an evolution in this model that suggests an inherent plasticity to CSCs that is mediated through the TME, arguing against the unidirectionality of the CSCs models ( Chaffer et al, 2013 ; Sancho et al, 2015 ; Shimokawa et al, 2017 ; Ahmed et al, 2018 ; Yao et al, 2019 ; Heise and Sommer 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… Molecules Cancer type Clinical outcomes Prognostic/ predictive utility Ref. D5D Non-small-cell lung cancer Higher expression in normal bronchial mucosa than tumor tissues Negatively associates with tumor size and histological grade Lower expression associates with shorter overall survival and disease-free survival Protective [27] D5D Esophageal squamous cell carcinoma Associates with better disease-free survival and overall survival Protective [28] D5D Bladder cancer Positively associates with tumor grade Enhances the proliferation Poor prognosis [13] D5D Laryngeal squamous cell carcinoma High expression and bioactivity in tumor tissues Undetermined [14] D5D rs174549 Oral cancer Correlates to a decreased risk of oral cancer Protective [37] D5D rs174548 Lung cancer Smoking-independent Particularly associates with lung cancer in women Undetermined [34] COX-2 Hypopharyngeal carcinoma Associates with chemoresistant Undetermined [38] COX-2 Colorectal cancer Relates to susceptibility to cancer in Caucasians Increased risk [39] COX-2 Osteosarcoma Higher expression in osteosarcoma than benign osteochondroma Associates with tumor grade, clinical stage, and metastasis Poor prognosis [40] COX-2 Breast cancer High expression associates with poor overall survival Poor prognosis …”
Section: D5d Implication In Pufa Related Diseases Including Cancermentioning
confidence: 99%